Sinergi Komunitas dan Teknologi Lokal Menghadapi Krisis Iklim - Muhamad Chairul Basrun Umanailo (PERSPEKTIF, 2026)
The climate crisis in East Nusa Tenggara has transformed from a mere weather anomaly to an existential threat to the food sovereignty of agrarian communities. In the midst of increasing subsistence precariousness, local communities are resisting through hybridization between traditional wisdom and technical innovation. This research aims to deconstruct the phenomenological form of the climate crisis and map the synergy between community social capacity and local technology in knitting resilience. This study uses a qualitative method with an interpretive phenomenological approach. Data were collected through in-depth interviews and participatory observations of key actors at the site level. Data analysis was carried out systematically using qualitative data analysis software (CAQDAS) to map inter-code relationships, narrative proxies, and co-emergence networks. The findings show that the climate crisis is physically experienced as the intensity of the disaster and the water crisis that directly hits the pillars of food affordability for citizens. However, communities respond through the activation of social capacity and local knowledge as a safety valve. Data network maps reveal a strong synergy where technical innovations are adopted and dissolved into local epistemology to create appropriate adaptation strategies. Future resilience in NTT does not depend on technocratic solutions alone, but on strengthening the synergy between technology and local wisdom.